Agency and Accountability in the Academic Reading of International Graduate Students Using English as an Additional Language - Altalouli, Mahmoud (Journal of International Students, 2021)
This grounded theory study explores the academic English reading practices of six English-as-an-additional-language students from China and Japan in a graduate course in their first semester at a U.S. university. Academic reading is an understudied yet foundational literacy practice for graduate students. Data include classroom observations of the graduate course during one semester, individual interviews with six students and the course instructor, and the collection of documents. Drawing on the analytic lenses of agency and accountability, the findings show that while the requirements established by the instructor and syllabus explicitly or implicitly held students accountable for the work, students also responded strategically to the course’s accountability structure. They agentively made choices about how to engage with the readings in terms of the purposes for which they read and how much time they spent on the readings.